Herbicides Efficacy against Volunteer Oilseed Rape as Influenced by Spray Solution pH - Monika Grzanka; Łukasz Sobiech; Grzegorz Skrzypczak; Tomasz Piechota (Agronomy, 2021)
The pH of the spray liquid is one of the factors influencing the efficacy of herbicides. Adjusting the appropriate parameters of the spraying liquid may reduce the consumption of pesticides, which is in line with the currently introduced legal standards and society’s requirements. In the greenhouse experiment, the influence of herbicides containing mesotrione, nicosulfuron, rimsulfuron, bromoxynil, and a mixture of nicosulfuron, rimsulfuron, and mesotrione on the efficacy of oilseed rape control was investigated. Oilseed rape (Brassica napus L. ssp. oleifera), apart from being an important crop, can become a nuisance weed in many fields as form of volunteer plants. Visual assessment, reduction of fresh weight, and chlorophyll fluorescence were performed. Individual herbicides influenced the tested parameters to a different extent. The pH of the spray liquid influenced the efficacy of individual plant protection products. The highest herbicidal efficacy in relation to the tested plants was observed in the case of combinations in which mesotrione was applied at a reduced and increased pH, nicosulfuron applied in an acidic and alkaline environment, rimsulfuron without pH modification, and all treatments in which bromoxynil was applied. The herbicides containing mesotrione and bromoxynil had the greatest impact on the photosystem II activity.